The force of knowledge : - Ziman, J. M. (Cambridge University Press, 1976)
Contents: In this 1976 volume, Professor Ziman paints a broad picture of science, and of its relations to the world in general. He sets the scene by the historical development of scientific research as a profession, the growth of scientific technologies out of the useful arts, the sources of invention and technical innovation, and the advent of Big Science. He then discusses the economics of research and development, the connections between science and war, the nature of science policy and the moral dilemmas of social responsibility in science. Each topic is introduced by reference to easily understandable particular examples, with a large number of illustrations chosen to bring out the concreteness and reality of science as a human activity. Professor Ziman gives a chapter-by-chapter list of suggested topics for oral and written discussion, intended to provoke critical, sceptical attitudes to simplified solutions to real issues, and comments briefly on relevant books and other sources.